Cover Picture: An Electrophilic Bromine Redox Catalysis for the Synthesis of Indole Alkaloid Building Blocks by Selective Aliphatic C−H Amination (Angew. Chem. Int. Ed. 48/2018). Issue 48 (12th November 2018) - Bergès, Julien; García, Belén; Muñiz, Kilian
Abstract : A giant step forward for bromine redox catalysis that enables intermolecular C−H amination reactions at previously inaccessible aliphatic positions is described by K. Muñiz et al. in their Communication onpage 15891 ff. The approach is based on the formation of anionic bromine(I) catalysts by the stoichiometric oxidation of ammonium bromides with a bisphthalimidato iodine(III) oxidant. Crystal structures of the catalysts reveal the bulky ammonium counterions to have a shape that is comparable to Giacometti′s famous bronze sculpture L ′homme qui marche .